Detection and Prevention of Hot Cracks during Laser Welding of Aluminium Alloys Using Advanced Simulation Methods - Komlodi, Attila (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2006)
Hot cracking, especially in alloys with increased hot crack susceptibility, is quite difficult to prevent, since there existed so far no adequate method to detect satisfactory welding parameters. Within this thesis a method, based on FE- simulations, is introduced, which can help the technologist to identify welding parameters advantageous to prevent hot cracking. Thus, with the help of this method time and costs can be saved during the technology desig